Estimation of Naproxen Related Substances in Sumatriptan Succinate and Naproxen Sodium Tablets by UPLC - Sripal Reddy, Palavai; Sait, Shakil; Kumar Hotha, Kishore (Asian Journal of Chemistry, 2013)
A novel isocratic reverse phase ultra performance liquid chromatographic method was developed and validated for quantitative determination of naproxen sodium and its four impurities in sumatriptan and naproxen sodium tablets. Chromatographic separation was achieved on Acquity CSH C18 100 mm × 2.1 mm, 1.7 μm with mobile phase milli-Q Water, acetonitrile and glacial acetic acid in the ratio of 50:50:1 (v/v/v) .The flow rate of the mobile phase was 0.5 mL/min naproxen and its impurities were monitored at 260 nm wavelength. The total run time was 10 min with in which all the impurities were well separated from naproxen sodium. Naproxen sodium was found to degrade significantly in acid and oxidative stress conditions and stable in base, water and photolytic stress conditions. The degradation products were well resolved from main peak. The developed method was validated as per ICH guidelines.